Effects of altering pedal cadence on cycling time-trial performance - Watson, G.; Swensen, T. (International Journal of Sports Medicine, 2006)
Our purpose was to examine the effects of altering cadence on 5-mile (8.045 km) time-trial (TT) performance in well-trained amateur male cyclists. Twelve cyclists (mean [SD] age: 24 [4] y; body mass: 70.9 [5.9] kg; and V·O2max: 4.56 [0.52] L · min-1) rode three 5-mile TT. The first was at their freely chosen or preferred cadence (PC); the other two, high cadence (HC; PC + 10.8 %) and low cadence (LC; PC - 9.2 %), were randomly assigned and completed in a counterbalanced crossover design. Subjects rode their own bicycles, fitted with a power meter, and attached to a windload simulator. Practice sessions were completed 2 d prior to each TT. Cadences for PC, LC, and HC were 92 (2), 83 (6), 101 (6) rpm, respectively; they were also significantly different from each other (p < 0.05). LC was 2.5 % faster than HC and more economical than HC and PC (66 [3], 69 [2], 71 [4 W · L-1O2 · min-1, respectively) (p = 0.05). LC heart rate and ventilatory efficiency (V·E/V·O2-ratio) were lower than PC counterparts, while LC and HC minute ventilation (V·E) were less than PC V·E (p < 0.05). LC may be the optimal cadence for 5 mile TT in well-trained amateur male cyclists because LC was the most economical, was faster than HC, resulted in the greatest proportion of fastest times (58 % vs. 25 % and 17 % for PC and HC, respectively), and elicited less cardiorespiratory strain than PC.